Implementation of Fingerscan Absence and Additional Employee Income (TPP) on Wort Behavior and Performance of Employees in Wara Utara District Office - Andhika Andhika; Muh. Yusuf Q; Suhardi M. Anwar (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
This research aims to determine (1) the effect of the implementation of finger scan attendance and TPP to the employee behavior and employee performance. (2) The relationship between the employee behavior and the employee performance. (3) The effect of the implementation of finger scan attendance and TPP on the employee performance by the employee behavior. (4) The effect of the implementation of finger scan and giving TPP simultaneously to the employee behavior. (5) The effect of the implementation of finger scan and giving TPP simultaneously to employee performance by employee behavior. This research uses a quantitative descriptive approach. The population and sample in this study were civil servants within the Wara Utara sub-district office and 6 (six) sub-districts under it, 52 people who were saturated samples. The data collection technique used in this study was through a questionnaire which was then analyzed by multiple linear regression analysis through the application of Statistical Product and Service Solution (SPSS) version 18.0 for windows. Based on the results of the analysis, it can be seen that: Y1 = 0.22X1 + 354X2 + 1, Y2 = 0.022X1 + 0.354X2 + 2 and Y2 = 0.022X1 + 0.354X2+ 0.529 +ɛ2. From this equation it can be concluded that